Paths of dissent : soldiers speak out against America's misguided wars - Bacevich, Andrew J.; Sjursen, Daniel A.; Edstrom, Erik; Damiani, Joy; Berschinski, Dan; Davis, Daniel L.; Scranton, Roy, 1976-; Jayamaha, Buddhika, 1971-; Dempsey, Jason K., 1972-; Emanuele, Vincent; Yingling, Paul; Hutto, Jonathan W., Sr; et al. (Metropolitan Books, Henry Holt and Company, 2022)
Fifteen original essays from American veterans of Iraq and Afghanistan offer first-hand perspectives on what made America's post-9/11 wars such costly and misguided exercises in futility, documenting how the world's self-proclaimed greatest military power went so badly astray.